Parents' role in providing mental health for children of bullying victims - Saadah, Muftahatus; Romadhon, Kharisma; Irfan, Irfan; Atin, Sri (Universitas Islam Negeri Ar-Raniry, 2023)
This study aimed to collaborate the role of parents in supporting the mental health of children who experience bullying. This research used a descriptive qualitative approach, based on data collection techniques, obtained from the results of interviews, observations, and literature studies as theories and supporting data. Data were analyzed systematically by steps such as searching, organizing, reducing, presenting, drawing conclusions, and verifying data obtained through observation, interviews, and data collection in the field. According to research findings, the forms of bullying mostly occurred were verbal (hurtful words) and physical treatments, both of which can degrade a child. The impact of bullying on victims included a decrease in children's self-confidence and children feeling less valuable to themselves. They also experienced feelings of resentment, closure, sadness, pressure from the surrounding environment, depression, anger, and discomfort, which causes them to doubt the presence of those around them. The role of parents is very important in fortifying the mental health of these children. Parents need to constantly approach their children, provide support, advice and help them develop strong mental resilience. In addition, parents must help children in giving a healthy perspective and children can accept well, one of the efforts of parents is to teach an attitude of never giving up, especially in pursuing higher education.